METHODS AND MEANS OF ORGANIZING INFORMATION SECURITY IT INFRASTRUCTURE - BIDIUK, OLEKSANDR; MARTSENKO, SERHII (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article explores the transformations in approaches and methods for organizing information security (IS) in the IT infrastructure of companies and businesses over the past five years. Key factors driving these changes include adaptations to critical situations such as the COVID-19 pandemic and the geopolitical tensions arising from russia’s military invasion of Ukraine. Additionally, the rapid evolution of software development teams and the DevOps methodology significantly alters traditional IT infrastructure management. The introduction emphasizes the impact of various factors on the organization of IS, particularly for assets deemed critical to the economy and state, which include a wide range of sectors such as energy, transportation, finance, and healthcare. The article identifies three main trends in the transformation of IS and IT infrastructure: the shifting geopolitics that redefine the perimeter of IT security, the rising demand for cloud solutions facilitating the migration of IT infrastructures, and the increasing adoption of container-based development for IT products. Further, the research highlights the growing significance of human factors in IS, pointing out that employee training and awareness about cybersecurity threats are crucial for strengthening overall information security posture. It also discusses the role of compliance with international standards and regulations, which can enhance organizational trust and improve risk management. Conclusion highlights the need for enhanced data protection mechanisms in cloud environments, the use of artificial intelligence for real-time threat detection and response, and the application of zero-trust models to mitigate risks, irrespective of user or resource location. Overall, the findings underlie the essential evolution of information security paradigms as businesses increasingly rely on digital frameworks, requiring an integrated approach to maintain security and resilience against cyber threats.